2021
DOI: 10.1039/d1ta03254b
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing void formation in all-solid-state batteries: the role of interfacial adhesion on alkali metal vacancy transport

Abstract: All-solid-state batteries containing a solid electrolyte and a lithium (Li) or sodium (Na) metal anode are a promising solution to simultaneously increase the energy density and safety of rechargeable batteries....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 89 publications
2
26
0
Order By: Relevance
“…[53] Yang et al demonstrated that for common Li-metal||SE interfaces, a W adhesion ¿ 0.7 J m −2 was required to prevent the formation of interfacial voids with the application of external pressure of 20-30 MPa. [29] Recently, Seymour and Aguadero [28] have developed a "bond breaking" approach and derived that if W adhesion > 2γ (where γ is the surface energy of Li or Na-metal), the formation of interfacial voids with potential loss of contact during the Li (or Na) stripping could be avoided. Our data suggest that among Li-based interfaces (Table S4), only the Li(100)||Li 2 O(110), Li(100)||Li 3 N(110) and Li(110)||Li 3 N(110) interfaces satisfy this criterion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[53] Yang et al demonstrated that for common Li-metal||SE interfaces, a W adhesion ¿ 0.7 J m −2 was required to prevent the formation of interfacial voids with the application of external pressure of 20-30 MPa. [29] Recently, Seymour and Aguadero [28] have developed a "bond breaking" approach and derived that if W adhesion > 2γ (where γ is the surface energy of Li or Na-metal), the formation of interfacial voids with potential loss of contact during the Li (or Na) stripping could be avoided. Our data suggest that among Li-based interfaces (Table S4), only the Li(100)||Li 2 O(110), Li(100)||Li 3 N(110) and Li(110)||Li 3 N(110) interfaces satisfy this criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the effects of stability of heterogeneous interfaces on the Li-ion transport properties. [27][28][29] Yang and Qi [27] have proposed that an interface with good adhesion, i.e. "lithiophilic interface" can result in a faster critical stripping current density, which is crucial to prevent dendrite growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the critical current for voiding also depends on the mechanical properties of the metal anode [16,17,41,42]. Voiding occurs when the flux of ions away from the interface current load exceeds the transport of metal atoms to the interface [13,43,44].…”
Section: Critical Currents For Plating and Strippingmentioning
confidence: 99%
“…Cycling was carried out at 20 °C under a 2.5 MPa stack-pressure, moving 0.5 mA•h/cm 2 capacity each half cycle, beginning by plating the working electrode (and stripping the counter electrode). Cell polarisation when stripping at 3 mA/cm 2 indicates voiding at the K/K-beta"alumina interface depends on the adhesion of the metal anode to the solid electrolyte [42], and dendrite growth depends not only on the properties of the metal anode but also on the properties of the SE [33][34][35].…”
Section: Critical Currents For Plating and Strippingmentioning
confidence: 99%